Students' Attitudes Toward the Use of Edtech as a Powerful Pronunciation Learning Tool in EFL - Tuhfatul Mubarokah Assalamah; Intan Fitri Hilza; Laili Hibatin Wafiroh (FKIP, Universitas Palangka Raya, 2024)
Effective pronunciation requires more than comprehension. Considering the increasing significance of AI apps, it is imperative to conduct thorough study to evaluate students' opinions towards the ELSA (English Language Speech Assistant) Speak app in English as a Foreign Language (EFL) lessons, specifically in relation to improving pronunciation. Prior studies indicated that students had negative attitudes towards learning English as a foreign language (EFL) due to repetitive textual resources. This research recommends including the ELSA Speak application into English as a Foreign Language (EFL) classroom. This research investigates the utilization of the ELSA Speak application by 20 primary pupils at a B1 proficiency level, with the aim of enhancing their pronunciation skills. Observations and interviews are employed to examine cognitive, emotional, and behavioral components as well as issues related to the ELSA Speak app. The findings suggest that students possess a positive cognitive perspective and are capable of comprehending and incorporating oral pronunciations. The ELSA Speak application encourages the development of analytical thinking and precise articulation. This study highlights the imperative for dynamic language learning methodologies that include cutting-edge technology.